al-Mahārat al-Iṭṭiṣālīyah al-‘Arabīyah fī ‘Amaliyat al-Ta‘līm wa-al-Ta‘allum fī al-Madāris al-Dīnīyah bi-Mālīziyā - Ishaq, Amiruddin; Muhammad Hilmi Abdullah; Zarima Muhammad Zakaria; Ramlah Ja'far (Al-Ma'rifah, 2019)
In Arabic learning, students often experience communication disruption due to weakness in mastering the language. To reach the meaning of his speech, the student will continue his utterance by using alternatives to successfully deliver the math. This effort is known as a communication strategy. This study attempts to identify and analyze the efforts and strategies used by the students who communicate in Arabic. This study was conducted on religious secondary school students in Malaysia. This study focuses on oral communication strategies. Some methods are used to obtain data. The researcher make audio and video recordings on all activities performed by students and then transcribed to identify the communication strategies contained in their speeches. In addition, observation methods, library studies and questionnaires were also used. The results of this research study, the researcher can identify the communication strategies used by the students and divide them into three main categories, mother language-based strategies, second language-based (Arabic) strategies and nonverbal language-based strategies. The findings of this study can help students to be convinced to speak Arabic and make it a habit despite language weaknesses and mistakes. By using the appropriate communication strategies, they can overcome language problems and facilitate communication and delivery of information in Arabic.